Identifikasi jenis batuan menggunakan inversi marquardt data geolistrik tahanan jenis konfigurasi dipole-dipole Bukit Lantiak Kecamatan Padang Selatan (Identify rock types using inversion marquardt geoelectrical data resistivity dipole-dipole configuration in Bukit Lantiak, Padang Selatan District) - Jemmy Rohmana; - Akmam; - Mahrizal (Department of Physics – Universitas Negeri Padang UNP, 2015)
The purpose of this research was to describe the type and the depth of rocks in Bukit Lantiak Padang Selatan. The type and the depth of rocks was needed to minimize the hazard caused landslide in the research area. This research use geophysical exploration method. Equipment that use was Automatic Resistivity (ARES) with Dipole-dipole configuration. The interpretation of the data in this research uses Marquardt inversion method to process the measurement data. Data was interpreted to get resistivity value and depth of rock in 2D model cross section below the earth surface. Result of this research indicates the type of rocks in Bukit Lantiak Padang Selatan is Andesite, Sandstone, Limestone, and Clay. These results indicate that the slopes of Bukit Lantiak composed by a mixture of hard rock layers that Andesite with soft rock layers that Clay and Sandstone. It show that Bukit Lantiak area have rock layers that are susceptible to landslides